Evaluasi Persediaan Perishable Raw Material Pada Industri Kecil Menengah Makanan Olahan Menggunakan Multi-Item Economic Order Quantity - Syahmer, Verra; Rishelin, Nadya; Nata, Refky Adi (Politeknik ATI Padang, 2024)
Raw material inventory is a crucial aspect of a business, as it can significantly affect the costs incurred. One type of raw material is perishable raw material, which, due to its nature, relates to shelf life and can impact not only the quantity of inventory but also inventory costs. One business that utilizes perishable raw materials is the small and medium-sized enterprise (SME) producing serundeng, using sweet potatoes and ghost peppers as perishable raw materials. The use of easily spoilable raw materials can be detrimental to SMEs if not managed properly. To avoid losses and improve efficiency, an analysis will be conducted by calculating inventory control. This research employs the multi-item Economic Order Quantity (EOQ) method, considering expiration dates and quantity discounts. The final outcome of the research includes a comparison of inventory levels between conventional methods and the proposed method, along with an analysis of the management implications of the findings. The results indicate that the total inventory costs without utilizing inventory control methods are higher than those using inventory management techniques. Therefore, this study provides insights to SMEs that effective inventory control can help the company not only reduce expenses but also increase revenue.